The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph182111491
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical Soft Tissue Trauma during Spontaneous Vaginal Birth in the Romanian Adolescent Population—Multicentric Comparative Study with Adult Population

Abstract: Romania is a country with high rates of adolescent births, associating scarce comprehensive obstetrical management with this specific population. This research aims to assess soft tissue trauma after vaginal birth in teenage mothers compared to their adult counterparts. A retrospective case-control study was conducted for one year in two hospitals. All vaginal deliveries were considered; the age cut-off value was considered at 20 years old for case and control groups. Lacerations were divided into three subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…He assessed clinical features, outcomes of diagnostic modalities, and initial response to therapy to determine their usefulness in predicting SI [ 1 ]. Matei et al conducted a one-year retrospective case-control study at two hospitals to evaluate soft tissue trauma after vaginal delivery in adolescent mothers compared with adult mothers [ 2 ]. Hampp et al compared the extent of soft tissue trauma maintained by robotic arm-assisted PKA and manual PKA in knee arthroplasty [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…He assessed clinical features, outcomes of diagnostic modalities, and initial response to therapy to determine their usefulness in predicting SI [ 1 ]. Matei et al conducted a one-year retrospective case-control study at two hospitals to evaluate soft tissue trauma after vaginal delivery in adolescent mothers compared with adult mothers [ 2 ]. Hampp et al compared the extent of soft tissue trauma maintained by robotic arm-assisted PKA and manual PKA in knee arthroplasty [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in keeping with the results of a retrospective study carried out in Romania with 1,498 parturient women, of whom 298 were adolescents, between 2020 and 2021, which found 89% higher odds of laceration among adolescents when compared to adults. 10 Greater f requency of perineal laceration during adolescence can be attributed to the immaturity of pelvic bone growth and muscle development, leading to a reduction in the internal diameters of the pelvis and the muscular strength of the pelvic floor, increasing the risk of adverse birth outcomes, such as perineal laceration. 11 We found that living in the North and Northeast regions of Brazil was associated with lower prevalence of laceration based on the perception of the postpartum women.…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados concordam com resultados de um estudo retrospectivo realizado na Romênia com 1.498 parturientes, das quais 298 adolescentes, entre 2020 e 2021, que observou chance de laceração 89% maior entre as adolescentes quando comparadas às adultas. 10 A maior frequência de laceração perineal durante a adolescência pode ser atribuída à imaturidade do crescimento ósseo pélvico e do desenvolvimento muscular, propiciando redução dos diâmetros internos da pelve e da força muscular do AP, aumentando risco de desfechos adversos no parto, como a laceração perineal. 11 Observou-se que residir nas regiões Norte e Nordeste do país esteve associada à menor prevalência de laceração baseada na percepção da puérpera.…”
Section: Figura 2 -Fluxograma Relativo àS Exclusões E Amostraunclassified